Developing and Testing a Real-Time Polymerase Chain Reaction to Identify and Quantify Bovine Respiratory Syncytial Viruses - Nefedchenko, A. V. (Mol Gen Microbiol Virol, 2021)
The bovine respiratory syncytial virus (BRSV) known as Bovine orthopneumovirus according to the international classification is one of the most important etiological agents of respiratory diseases in calves. At present, rapid and reliable methods to detect and measure the concentrations of this pathogen are needed. The objectives of the survey are developing the real-time polymerase chain reaction (PCR) to identify and quantify the BRSV RNA and, based on it, determining the number of the virus genomes in the respiratory tract of sick animals during the disease outbreaks. The nucleocapsid (N) protein gene of the virus served as the target for amplification. Messenger RNA (mRNA) of bovine GAPDH was used as a reference gene. A panel of positive control samples at known concentrations was used to estimate the virus and GAPDH numbers. The concentration of viral RNA extracted from the biomaterial samples was quantified relative to the bovine GAPDH mRNA level. The analytical sensitivity of PCR demonstrating high specificity and reproducibility was 1 × 10(3) genome equivalents per 1 cm(3). All 273 samples of biological material taken from the animals with the respiratory diseases were analyzed. The virus genome was detected in 19.4% of samples. The viral RNA was more frequently detected in the lungs, which comprised 10.61% of positive samples. It was less frequently found in the mucous membranes of trachea and bronchi and the lymph nodes of the lungs, which comprised 0.73% of positive samples each. Concentrations of the virus in samples varied. The highest concentration was recorded in the lungs (1.3 ± 0.5—4.8 ± 0.47 log(10) copies of BRSV/GAPDH RNA). The developed test kit may be used to quantify the concentration of the bovine respiratory syncytial virus in disease pathogenesis and to estimate the efficiency of vaccine or antivirus preparations for animals.